Development of Coronavirus Disease Patient Registration Information System with Object Oriented System Approach - Riyanto Riyanto; Mustar Aman; Beby Tiara; Nuri Wiyono; Yunianto Agung Nugroho (Journal of Information System and Informatics, 2021)
The rapid development of Information and Communication Technology (ICT), it certainly has a big impact on very significant changes in various fields. Hospitals are health service institutions that provide complete individual health services that provide inpatient, outpatient, and emergency services. emergency. Until now, the registration system for Coronavirus patients at the Tangerang Regency Hospital has not been maximized and has not displayed inpatient rooms for Coronavirus patients. The problem that occurs in the Coronavirus patient registration system at the Tangerang Regency Hospital is that it is not yet computerized or web-based because the Coronavirus patient registration process is still using the Microsoft Excel application, patient data processing is still conventional and the list of Coronavirus patients has not been detailed, patients who have already registered, it turns out that there are no inpatient rooms available so that many Coronavirus patients are slow to be helped. The aim of the research is to build a fast and accurate Coronavirus patient registration system. The research method used is descriptive qualitative. Data collection techniques were carried out by means of observation, interviews, and literature study. The results of this study are in the form of software, namely a web-based Coronavirus patient registration system that can display detailed information on Coronavirus patient registration and Hospital location maps.